Hepatoprotective Potential of Malus domestica Seed Oil Against Thioacetamide-Induced Toxicity in Rats: Biochemical, Histopathological, and In silico Study - Alghamdi, Rayan; Al-Attar, Atef; Alomar, Mohammed; Alghamdi, Yousef; Almuntashiri, Saleh; Alzahrani, Dhaifallah; Abu Zeid, Isam (Journal of Biological Insights, 2026)
Thioacetamide (TAA) is a firmly established hepatotoxic substance commonly employed to induce experimental liver injury. This study investigated the possibility defensive consequences of Malus domestica (apple) seed oil against TAA-induced hepatotoxicity in male Wistar rats, supported by biochemical, histopathological, and molecular docking analyses. Forty rats were arbitrarily assigned into four groups: control, TAA, TAA + Malus domestica oil, and Malus domestica oil only. TAA was administered intraperitoneally (300 mg/kg, twice weekly) for 7 weeks, whereas Malus domestica seed oil was given orally (800 mg/kg/day). TAA exposure caused significant elevations in alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), and total bilirubin, along with marked reductions in total protein and albumin, accompanied by profound histopathological alterations. Supplementation Malus domestica seed oil significantly improved these modifications, reinstating liver function and preserving hepatic architecture. Molecular docking further revealed strong binding affinities of key phytochemicals such as phlorizin, procyanidin, corosolic acid, and aglycone with inflammatory and fibrotic proteins (TNF-α and TGFβR-1), supporting their hepatoprotective potential. Collectively, these findings propose that Malus domestica seed oil may represent a promising natural therapeutic candidate for mitigating chemically induced liver injury and warrant further preclinical and clinical investigations.